2016
DOI: 10.1016/j.gde.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the adult Drosophila intestine: all roads lead to homeostasis

Abstract: Maintenance of tissue homeostasis is critical in tissues with high turnover such as the intestinal epithelium. The intestinal epithelium is under constant cellular assault due to its digestive functions and its function as a barrier to chemical and bacterial insults. The resulting high rate of cellular turnover necessitates highly controlled mechanisms of regeneration to maintain the integrity of the tissue over the lifetime of the organism. Transient increase in stem cell proliferation is a commonly used and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 62 publications
0
84
1
Order By: Relevance
“…To investigate what damage-induced signals activate the RSCs, we examined damage pathways known to activate ISC proliferation. Extensive studies have shown that the EGFR/MAPK, Jak/Stat, Wnt, Hippo, PVF, JNK, Insulin, and BMP pathways are all involved in eliciting ISC division either under steady state conditions or during regeneration following cellular damage (Gervais and Bardin, 2017;Guo et al, 2016;Jiang et al, 2016;Li and Jasper, 2016). Reporters for four of these pathways, JNK, Jak/Stat, MAPK and Yki pathways were induced upon surgical injury ( Figure S3).…”
Section: Damage Activates Quiescent Rscs Via Upregulation Of Multiplementioning
confidence: 99%
“…To investigate what damage-induced signals activate the RSCs, we examined damage pathways known to activate ISC proliferation. Extensive studies have shown that the EGFR/MAPK, Jak/Stat, Wnt, Hippo, PVF, JNK, Insulin, and BMP pathways are all involved in eliciting ISC division either under steady state conditions or during regeneration following cellular damage (Gervais and Bardin, 2017;Guo et al, 2016;Jiang et al, 2016;Li and Jasper, 2016). Reporters for four of these pathways, JNK, Jak/Stat, MAPK and Yki pathways were induced upon surgical injury ( Figure S3).…”
Section: Damage Activates Quiescent Rscs Via Upregulation Of Multiplementioning
confidence: 99%
“…A Ret/wingless positive feedback loop promotes stem cell proliferation in the adult Drosophila intestine Several mitogenic signals have been shown to promote stem cell proliferation when mis-or over-expressed from adult intestinal progenitors (Jiang & Edgar, 2012;Guo et al, 2016;Jiang et al, 2016). To begin to explore the signalling context in which Ret may function, we tested the ability of such mitogens to stimulate proliferation of adult intestinal progenitors with reduced Ret expression.…”
Section: Ret Sustains Stem Cell Proliferation In the Adult Drosophilamentioning
confidence: 99%
“…The Drosophila adult gut is made up of three cell types: differentiated enterocytes (ECs), entero-endocrine cells (EEs), and intestinal stem cells (ISCs) (Figure 1A-B, (34)). Expression of a phosphorylation-defective and therefore constitutively active form of Yki in the ISCs ( esg-Gal4 Gal80 ts > UAS-yki 3SA , referred to as esg ts >yki 3SA ) triggers ISC over-proliferation (32) (Figure 1C, Figure S1A), as revealed by increased 5-ethynyl-2 deoxyuridine (EdU) uptake (Figure S1B), Phospho-Histone H3 (PH3) staining (Figure S1C), and elevated expression of matrix metalloproteinase genes (MMPs) (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%